MENGKAJI RUANG LINGKUP PEKERJAAN MARKETING PUBLIC RELATIONS (MPR) DAN CORPORATE PUBLIC RELATIONS (CPR) - Melita, Yerah (Istek Widuri Jakarta, 2016)
Understanding the scope of work of Marketing Public Relations (MPR) and Corporate Public Relations (CPR) is important, because if the public relations or marketing practitioners do not understand the scope of their work, performance or results of their work becomes less than the maximum. It impacts on the efficiency and effectiveness of the company itself. Overlapping of work, wastage of time and the cost eventually the company will lose money, and it is not possible the company could go out of business. Overlapping of work, wastage of time and the cost eventually make losses of the company and it is not likely the company could shut downIt is necessary for the correct knowledge and understanding of the tasks and the work of each, both as MPR and CPR, so that both are mutually supportive, complementary and fill each other's deficiencies.